"The Big Women": A textual analysis of Chinese viewers' perception toward femvertising vlogs. Issue 3 (September 2020) - Duan, Xu
Video blogging (vlogging), a type of short video that people produce by recording and editing their daily lives, has become an emerging form of digital cultural production on social media platforms in China. With the profound growth of video marketing on social platforms, brands have increasingly leveraged vloggers to promote female-targeted products. This phenomenon becomes especially paradoxical when marketers bring the narrative of female empowerment into the discourse. This case study employed textual analysis to understand how Chinese viewers make sense of Bobbi Brown's "The Big Women" vlog endorsed by the female vlogger Zhuzi on Weibo. A typology of viewers' response was generated: (1) reciprocity of self-disclosure; (2) perceived interconnectedness with the vlogger; and (3) perceived women empowerment and advertisement effectiveness. The findings of this article articulate a symbolic form of relationship between content creators, brands, and consumers that promotes women empowerment. This study argues, however, that this perception of women empowerment may obscure the implicit consumerism embedded in the femvertising contents, while promoting the myth of self-empowerment through consumption. The findings of the study shed light on the rise of (pseudo-)feminism ethos constructed by the consumer market in contemporary China and beyond.